EXPERT ASSESSMENT OF EFFECTIVE MANAGEMENT STRATEGIES TO INDUSTRIAL RISKS - and (Municipal economy of cities. Series: «Economy science», 2013)
The article discusses the use of use of expert estimation of efficiency of strategy of management by production risks with application of a method of simple ranging is considered.